Lonely Elderly Persons: At the top of the Pyramid of Weakness in the age of Corona - Knežić, Branislava (Zbornik Instituta za kriminološka i sociološka istraživanja, 2022)
Based on the available literature and research, this paper briefly presents knowledge about the specifics of the elderly, which made them a particularly risky part of the population for contracting the coronavirus, as well as the negative consequences of "closure" and isolation, which led them to loneliness and helplessness. When care for the elderly is overemphasized verbally, it can become offensive, especially for someone who cares more about dignity than mere survival. In order to obtain data on the experience of people over the age of 65 regarding the state of emergency and restrictive measures, we conducted a survey in Belgrade, one year after the declaration of the COVID-19 pandemic. Twelve people were interviewed: 6 women and 6 men, aged 66 to 86 in March 2021. Transcripts of semi-structured interviews were analyzed based on the principles of thematic analysis. It is known that on the basis of a small, convenient sample, generalizations cannot be made, but the original words of the interviewees provide a deeper and more layered description of the immediate reality. Isolation, separation from children, extended family and friends, confusion in information and attempts at intimidation through all media were experienced more often as punishment and stigmatization than as care and protection from infection and disease.